Tissue Engineering in Achilles Tendon Reconstruction: A Systematic Review of Preclincal Studies - Mir, Saqib; Mafi, Reza; Mafi, Pouya; Khan, Wasim (Current Stem Cell Research & Therapy, 2018)
Background: Tissue engineering is now being used in Achilles tendon (AT) repair in animal models. There are many preclinical studies that have used different types of stem cells for AT repair. However, there are no systematic reviews that evaluate all these studies to see which type of stem cell provides the most improvement for AT repair in animal models. Sahni V et al.,(1) divided the multiple stem cell types into three broad categories; Tendon derived stem cells (TDSCs), mesenchymal stem cells (MSCs) and embryonic stem cells (ESCs). These three categories have been used in this systematic review to group the different stem cell types together and to also see which category of stem cells provide superior enhancement of AT repair. Method: All studies that have focused on using different types of stem cells in animal models for AT repair and have also included an outcome measure to identify any improvement made with stem cells have been included in this systematic review. Online published articles from 1946 to January 2016 were searched using Ovid MEDLINE (R) and PubMed databases. Results: Of the 181 articles found and assessed for eligibility, 15 articles met predefined selection criteria and were included in this systematic review. Stem cells can either augment current methods of surgical repair or can provide an alternative route for tendon regeneration because of their unique ability of improving histological characteristics and biomechanical properties. Conclusion: This systematic review shows that stem cells can provide an improvement in AT repair in animal models. Histological analysis of the tendon tissue as well as biomechanical tests such as ultimate failure load have been used to show this improvement in AT repair. Nevertheless, we do not know which type of stem cell, from the three broad categories, provides a superior enhancement of AT regeneration in animal models. Our results underscore a need for a head-to-head comparison of the different types of stem cells used in AT repair with or without current methods of surgical repair.
Keywords: surgical repair